2019
DOI: 10.1016/j.apsusc.2018.10.099
|View full text |Cite
|
Sign up to set email alerts
|

Long term superhydrophobic and hybrid superhydrophobic/superhydrophilic surfaces produced by laser surface micro/nano surface structuring

Abstract: Stable superhydrophobic and superhydrophilic surfaces were created using laser surface micro/nano patterning. These were based on periodic 3D micro/nanostructures produced on 316L stainless steel over large areas using nanosecond and picosecond laser surface fabrication. The effects of laser processing parameters on controlling the micro-/nano-topographical characteristics of 24 different types of structures were presented. Surface roughness, surface chemical composition and wettability (via water contact angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 46 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…As we focused on examine the laser treated surface after one day and one month of laser treatment, the EDX results showed that the carbon percentage increased with time. Indeed, it was reported by our previous work that the carbon layer was decreased by immersing the surfaces in water [24]. Therefore, the best explanation for the mechanism involved is that these carbon layer is related to the adsorption of the organic component from the atmosphere onto the laser produced oxide surface [36][37][38].…”
Section: Characterisation Of Surface Chemistry and Wettabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…As we focused on examine the laser treated surface after one day and one month of laser treatment, the EDX results showed that the carbon percentage increased with time. Indeed, it was reported by our previous work that the carbon layer was decreased by immersing the surfaces in water [24]. Therefore, the best explanation for the mechanism involved is that these carbon layer is related to the adsorption of the organic component from the atmosphere onto the laser produced oxide surface [36][37][38].…”
Section: Characterisation Of Surface Chemistry and Wettabilitymentioning
confidence: 96%
“…Such decreases in the surfaces wettability can be significant altered directly after laser treatment, due to the adsorption of organic and carbon contents onto the surface from the atmosphere [23]. In order to control such changes in the surface wettability and energy, surface may be chemically treated following laser ablation [15,[20][21][22]24]. In this work, the effect of laser generated structures with and without chemical modification and their effect on bacterial retention over time was characterised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser micro-and nanomachining can also be used to generate asperities on surfaces which behave as hydrophobic or superhydrophobic depending on the base material, the type of microstructure created, the processing atmosphere and the laser machining parameters. [57][58][59][60] Both laser-induced periodic surface structures (LIPSS) and unstructured bumps can be generated over surfaces using various kinds of pulse lasers, such as nano- 61 or femtosecond lasers, 62 and so on, just by varying various laser parameters. 63 Figure 22 shows SEM images of laser-patterned surfaces under different machining conditions.…”
Section: Multistep Processesmentioning
confidence: 99%
“…Many previous papers reported that surface topography and surface chemistry contributed to the super-hydrophobicity of the laser ablated surfaces [39,40]. However, the relationship between laser-induced surface topography and surface chemistry was seldom investigated.…”
Section: Introductionmentioning
confidence: 99%